The Synergistic Responses of Different Photoprotective Pathways in Dwarf Bamboo (Fargesia rufa) to Drought and Subsequent Rewatering - Liu, Chenggang; Wang, Yanjie; Pan, Kaiwen; Wang, Qingwei; Liang, Jin; Jin, Yanqiang; Tariq, Akash (Frontiers in Plant Science, 2017)
Dwarf bamboo-dominated forests are often subjected to temporary periods of drought due to rising air temperature and decreasing rainfall. Nevertheless, the relationship among CO2 assimilation, photoprotective pathways and metabolism of reactive oxygen species (ROS) remains unexplored in bamboo species. Changes in leaf gas exchange, chlorophyll fluorescence, energy partitioning, antioxidative system and compounds related to ROS metabolism in Fargesia rufa plants subjected to drought and subsequent rewatering were analyzed. Drought resulted in a reversible inhibition of photochemistry, particularly net CO2 assimilation, and lipid peroxidation due to ROS accumulation. Meanwhile, photoprotective pathways, including the water-water cycle (especially for moderate drought), and adjustment in antenna pigments, thermal dissipation and antioxidative defense capacity at organelle levels (especially for severe drought), were up-regulated at the stress phase. Conversely, photorespiration was down-regulated after drought. As a result, rewatering restored most of the photochemical activity under drought, especially moderate drought. Moreover, thermal dissipation under severe drought still operated for avoiding high ROS level after rewatering. Therefore, the synergistic function of these photoprotective pathways except photorespiration can protect the photosynthetic apparatus from oxidative damage in response to varying intensities of drought stress when CO2 assimilation is restricted. This is helpful for the gradual recovery of photosynthetic capacity after rewatering. Thus, F. rufa plants can withstand drought and is capable of survival in such environment.